2022
DOI: 10.1007/s10586-021-03428-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance prediction of deep learning applications training in GPU as a service systems

Abstract: growth rate of over 38% to support 3D models, animated video processing, and gaming. GPUaaS adoption will be also boosted by the use of graphics processing units (GPUs) to support Deep learning (DL) model training. Indeed, nowadays, the main cloud providers already offer in their catalogs GPU-based virtual machines pre-installed with the popular DL framework (like Torch, PyTorch, TensorFlow, and Caffe) simplifying DL model programming operations.Motivated by these considerations, this paper studies GPU-deploye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In this work, ML models are adopted to correlate job and target VM features with the expected execution time. In particular, as discussed in [20], linear regression can be used to automatically build models that infer a deep network training time on a particular type of VM. A di erent prediction model is built in [20] for each type of neural network.…”
Section: Models For Predicting Training Jobs Performancementioning
confidence: 99%
See 3 more Smart Citations
“…In this work, ML models are adopted to correlate job and target VM features with the expected execution time. In particular, as discussed in [20], linear regression can be used to automatically build models that infer a deep network training time on a particular type of VM. A di erent prediction model is built in [20] for each type of neural network.…”
Section: Models For Predicting Training Jobs Performancementioning
confidence: 99%
“…In particular, as discussed in [20], linear regression can be used to automatically build models that infer a deep network training time on a particular type of VM. A di erent prediction model is built in [20] for each type of neural network. The considered features related to the characteristics of the training jobs are the number of iterations and the batch size.…”
Section: Models For Predicting Training Jobs Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Their remarkable predicting capabilities can assist the user in accurately predicting resource usage, execution times, etc. Indeed, previous work [11]- [17] has shown that ML models are usually able to predict these target quantities with very small validation error.…”
Section: Introductionmentioning
confidence: 99%